Los cuentos como estrategias didáctica y la expresión oral en la enseñanza remota en niños de cinco años en la Institución Educativa Inicial Victoria Barcia Boniffatti, Iquitos 2021 - Gonzales Flores, Litta (2023)
In 2021, the main objective of this research was to determine the effectiveness of the use of narratives as a didactic tool and means of oral expression through distance education for the students of the Victoria Barcia Boniffatti Initial Educational Institution of Iquitos, who are only five years old. For the methodological section, relational research was used with a cross-sectional, bivariate and field design. There were 133 children, all five years old, from the designated institution who constituted the population and the sample of the study. Two observation forms were prepared, and observation was used to collect the information. Before collecting the data, the instruments were submitted to expert judgment for validation. The students showed a strong and statistically significant positive correlation between the use of stories as a didactic strategy and the use of oral expression in distance education (Spearman's Rho = 0.772**, p-value = 0.000).